Constitutive activity of N-β-alanyl-catecholamine ligase in insect brain - Pérez, Martín Mariano (2004)
N-Beta-Alanyldopamine (NBAD) is the primary catechol tanning agent precursor in typical brown or yellow insect cuticle. The insect integument enzyme responsible for the synthesis of NBAD was reported to be expressed solely in the epidermis, and only at the time of cuticle sclerotization. However, in this study we demonstrate directly that the enzyme also is expressed in a constitutive manner in the neural system of insects. The requirements and kinetic parameters of the brain-associated enzyme appear similar to those of the epidermis-associated enzyme in Ceratitis capitata. The brain-associated enzyme also was able to catalyze the in vitro synthesis of N-beta-alanylnorepinephrine (NBANE) and beta-alanyl derivatives of other biogenic amines. A melanic mutant of C. capitata, niger, was unable to conjugate beta-alanine with dopamine or other amines in either the epidermis or the brain. This result strongly supports the idea that these enzymes actually are expressed from a single gene and that differences in regulation must exist that account for the constitutive expression in the neural system. Similar results were obtained in Drosophila melanogaster and other insects. From these data, a number of questions arise about the role of beta-alanyl derivatives of biogenic amines and other compounds in insect brain and similarly, in the mammalian CNS.